Decoration of PdAg Dual-Metallic Alloy Nanoparticles on Z-Scheme α-Fe2O3/CdS for Manipulable Products via Photocatalytic Reduction of Carbon Dioxide - Yang, Shuhui; Ke, Xi; Zhang, Menglong; Luo, Dongxiang (Frontiers in Chemistry, 2022)
Metal nanoparticles have been extensively used as co-catalysts in photocatalytic systems in order to pursue improvements in both reaction kinetics and selectivity. In this work, PdAg dual-metallic nanoparticles synthesized by the co-reduction method were decorated on a well-established α-Fe2O3/CdS Z-scheme photoactive material as a co-catalyst to study their performance for promoting the photoreduction of CO2. Herein, α-Fe2O3 and CdS were in situ synthesized on fluorine-doped tin oxide (FTO) glass by hydrothermal and SILAR (successive ionic layer adsorption and reaction) methods, respectively. The direct Z-scheme charge transfer path between Fe2O3 and CdS and the effective electron migration toward the PdAg mainly contributed to the excellent photocatalytic CO2 reduction performance. The controllable work function based on Pd (5.12) and Ag (4.26) constructed an appropriate band alignment with α-Fe2O3/CdS and displayed favorable production for CH4 rather than CO. The optimum ratio of PdAg 1:2 performed a 48% enhancement than pure Pd for photoreduction of CO2. Meanwhile, the enhanced charge separation improved the photoelectrochemical performance and photocurrent generation, and reduced the electrical resistance between components. This work provided insights into the dual-metallic co-catalyst for boosting the activity and selectivity of photocatalytic CO2 reduction.